A mathematical interpretation of the communicative constitution of organizations. Issue 2 (4th May 2022) - Schwing, Kyle M.; Spitaletta, Jason; Pitt, Jonathan
ABSTRACT: We propose a probabilistic control-system model to measure gradations of organizational coherence. Our model expresses the four flows of the Communicative Constitution of Organizations, and moves beyond common network-based analyses to quantify the emergence of organization through communication. In the model, an organization's leadership selects from a set of discrete strategies, the number and complexity of which are regulated by membership negotiation and self-structuring. Activity coordination constrains the internal response of the organization to the selected strategy, and institutional positioning shapes its ultimate outcome in the environment. Our model introduces a new partition of the four flows between those that affect the set of available strategies versus the precision of organizational control. The model informs proxy measurements of the maturation of a partial organization, such as an insurgency. Its quantified approach enables testing of the interrelationships and tradeoffs among flows in an agent-based simulation of varying levels of partial organizations competing and cooperatively exploring for resources. The most consequential flow in our scenario, measured in comparison to baseline data, is membership negotiation. Complex behaviours emerge in simulation results, such as information asymmetries, tradeoffs between power and efficiency, the contrast between short- and long-term gains, and individual versus group utility.